KARAKTERISTIK PENAFSIRAN MUHAMMAD ‘ALI AL-SHABUNIY DALAM KITAB SHAFWAH AL-TAFÂSÎR - Rahmad Sani (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2018)
This simple article describes the characteristics of Muhammad ‘Ali al-Shabuniy's interpretation in the book Safwah al-Tafâsîr. This discussion is qualitative in nature with a focus on his work, especially in the book Safwah al-Tafasir. This paper analyzes the characteristics of Muhammad ‘Ali al-Shabuniy's interpretation in the book Safwah al-Tafâsîr in the form of stages, methods and patterns of interpretation. From the results of the research conducted it can be concluded that Muhammad 'Ali al-Shabuniy used seven stages in interpreting the Qur'an, namely: Explaining the contents of the letter, munasabah, al-lughah, asbâb al-nuzûl, al-tafsîr, balaghah, and lesson or wisdom contained in the verse. The method of interpretation contained in the book Safwah al-Tafâsîr is the method of tahlîlî and the style of interpretation is adabi wa al-ijtimâ'i.